Tinjauan Historis Kecerdasan Buatan Dalam Games - Troy Troy (Institut Seni Indonesia Yogyakarta, 2015)
Video games experienced rapid development in terms of gameplay, level of difficulty, and artificial intelligence. Artificial intelligence in computer games devoted to the ability to control the elements in the game that make intelligent decisions when a state has several options with different outcomes, resulting in behaviors that are relevant, effective, and useful. In the video game, scoring as well as compliance with the rules and visual display is presented by computers, not by humans. Computers also control the enemy character in the game, becoming another participant, acting as referee, as well as the condition of an area